Improving the Management Mechanism of Tourist- Recreation Activities in Uzbekistan Based on Multi-Factor Models (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article explores the methodological aspects of management of the tourism and recreation sector, which is able to rapidly develop the national economy of Uzbekistan. In the process of theoretical research, developed the author's definition of the specific category tourist-recreation on the basis of the study of the research of foreign and local scientists.In the article, based on the analysis of the level of use of the potential of tourist recreation facilities in Uzbekistan, has been improved the mechanism of digital reservation of tourist recreation services on the basis of digital management platforms and recommended for practical use.By using the econometric model representing the private situation in Uzbekistan, calculated the forecast indicators for 2022-2025 years. Evaluated the quality of the econometric model and the quality of the model parameters within the framework of the main criteria.